Asuhan Kebidanan Continuity of Care Ny.N Usia 29 Tahun di Puskesmas Lambu - Suryani, Lilis; Salafas, Eti (Universitas Ngudi Waluyo, 2024)
Continuity Of Care is a service that is achieved when there is a continuous relationship between a woman and a midwife. Continuous care related to health professionals, midwifery services are carried out from preconception, early pregnancy, during all trimesters, birth and childbirth to the first 6 weeks postpartum until deciding to use family planning. This aims to help, monitor, and detect the possibility of complications that accompany the mother and baby from pregnancy to the use of birth control. The method of midwifery care at the Lambu Health Center is through home visits and visits at the Health Center by providing counseling according to the needs of mothers. Midwifery care given to Mrs.